Stališča vzgojiteljev do zgodnje pismenosti v Sloveniji - Skubic, Darija (Revija za elementarno izobraževanje, 2012)
Pre-school teachers´ viewpoints on early literacy in Slovenia. The article discusses early literacy in Slovenia. It is divided into two parts. The first part defines the terms literacy (from the historical perspective) and early literacy. Further on, the author introduces early literacy as interpreted within the Kindergarten Curriculum, and some guidelines regarding early literacy in kindergartens, recommended by OECD (OECD, 2001, 2002, 2006) and The White Paper on Education in the Republic of Slovenia (2011). The second part comprises a research study regarding the viewpoints of pre-school teachers from nine arbitrarily selected Slovene kindergartens on early literacy in Slovenia and their suggestions on how to improve the current situation with respect to early literacy. The concluding observations point to certain directions to improve the language practice in Slovenian kindergartens, which regards early literacy.